Dynamic System Model of Beach Tourism Management in Hukurila Village, Ambon - Talakua, Eygner Gerald; Papilaya, Renoldy Lamberthy (E-Journal of Tourism; Volume 12 Number 1 (March 2025)DO - 10.24922/eot.v12i1.126128, 2025)
One of the leading tourist objects in Ambon, Indonesia, is the beach tourism of Hukurila Village. The potential of coastal, fisheries and marine resources and community support are the important assets in its beach tourism. Behind the potentials there are still shortcomings, and they are necessary to improve. An important question to study is how is the model for managing beach tourism in Hukurila Village, Ambon? The survey was conducted on a sample size determined from tourists, tourism area managers, and the village's government through incidental sampling and snowball sampling techniques. Data were analyzed by using the system dynamic model method with seven supporting methods. The results showed that: a dynamic system model for managing beach tourism in Hukurila Village, Ambon can be built from data of the number of tourist visits, the carrying capacity of the area, the carrying capacity of tourism utilization, the suitability of beach tourism, the economic value of tourism, and the willingness to pay of tourists. Simulation and validation of the model show that all data or variables used are valid. The model is dynamic and produces four policy programs that is: increasing the number of tourists visits every year, increasing the quality and quantity of tourism products continuously according to the carrying capacity of the area or the carrying capacity of utilization, gradually increasing tourist tariffs, and making a breakwater in the coastal tourism area. Assistance is needed in implementing policy programs so that the mission of becoming a sustainable tourism village can be realized in Hukurila Village.